Predictor of purnawidya performance post training of wound care blended learning method in DKI Jakarta - Haerani Idah (Monas: Jurnal Inovasi Aparatur, 2021)
The COVID-19 pandemic situation has hampered wound care services. Apart from contact restrictions, patient and family anxiety to visit hospitals and health workers having diabetic wound care skills are still inadequate. Only 1 unit of First Level Health Facility (FKTP) has succeeded in developing a diabetic wound care polyclinic; thus, the percentage of diabetic wound sufferers who receive standard services is only 1 percent. This study aims to determine predictors of graduate performance after wound care training with blended learning methods in Jakarta Province in 2021. Descriptive quantitative method using a cross-sectional approach and primary data were collected using structured questionnaire survey technique. The study was carried out from August to September 2021. The population was all 44 graduates of wound care training with the blended learning method. The result shows that the correlation value (r) between age and performance score was 0.43 with a P-value of 0.007. It means that there is a statistically significant relationship between age and the graduate performance score. There is also a significant relationship between motivation and performance scores, with the correlation value (r) between motivation scores and performance scores of 0.37, P-value of 0.020. The dominant factor that affects graduate performance is motivation, with a P-value of 0.02. The magnitude of the variation that affects the dependent variable is 0.129, meaning that the motivation variable can explain 12-13 percent of the variation in the graduate performance score.